E-Portfolio (Pathbrite) - Othman, Joharry (Centre for Professional Development (CPD), International Islamic University Malaysia., 2020)
Why PATHBRITE? It is one of the many online learning tools that have helped teachers and educators alike transform students into becoming active learners via the use of engaging and dynamic platforms, templates and big data analytics. It is known as a next generation portfolio or commonly called “e-portfolio tool”. It was launched in Austin, Texas in 2012 by a group of dedicated professionals, among them included creative educators.